Web-Based Information System for Monitoring and Evaluating the Quran Memorization of Tahfidz Students - Holida Izzatilla; Abd. Ghofur; Lukman Faqih Lidimilah (Universitas Islam Raden Rahmat, Malang, 2026)
The use of information technology in the Islamic boarding school environment, particularly in the Qur’an memorization program, is a crucial tool for improving the effectiveness of monitoring students’ progress. Currently, the management of memorization data at the Salafiyah Syafi’iyah Sukorejo Islamic Boarding School is still conducted conventionally, resulting in a high risk of data loss, inefficient report compilation, and a lack of transparency in information for students’ guardians. This study aims to design and implement a web-based memorization monitoring information system that integrates workflows among administrators, educators, and parents. System development employs the Software Development Life Cycle (SDLC) methodology using the Waterfall model, encompassing the stages of requirements analysis, architectural design, implementation using the Laravel framework, and system testing. Black-box testing results indicate that all system features functioned according to specifications, with a functional success rate of 100%. Additionally, white-box testing through conditional logic validation ensured that all program workflows, including the authentication module and target achievement calculations, operate stably. The main contribution of this research lies in the implementation of a personalized automatic notification mechanism, which allows guardians to monitor their children’s memorization progress in real-time while facilitating proactive coaching interventions.